The first Programmefood and nutrition security, impact, resilience, sustainability and transformation: Review and future directions (2020)
The FIRST Program – Food and Nutrition Security Impact, Resilience, Sustainability and Transformation, is a partnership between the European Union and FAO. The EU and FAO launched a stocktaking exercise to assess progress in improving food security and nutrition in 24 FIRST priority countries. This paper presents the results of a quantitative analyses, literature review, country reports and a May 2019 consensus workshop that were the basis of identifying issues that must be addressed for FIRST countries going forward. Seven thematic areas were emphasized as essential for meeting the targets in SDG2 – zero hunger. These factors include reinventing agriculture; unleashing the private sector; gender equity; decentralization of programs; multi sector concepts within a sector approach; prioritization; data, and political process and governance.